Analisis Dampak Volatilitas Nilai Tukar dan Kinerja UMKM di Indonesia Terhadap Ketahanan Pangan di Indonesia Pasca Pandemi Covid 19 - Abdul Aziz (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the impact of exchange rate volatility and the performance of Micro, Small and Medium Enterprises (MSMEs) on food inflation in post-COVID-19 pandemic Indonesia. Using a quantitative approach, secondary data from relevant institutions such as Bank Indonesia and FAO were analysed by logistic regression to evaluate the relationship between exchange rate fluctuations, MSME productivity, and food security. Results show that exchange rate volatility has no significant effect on food inflation, while MSME performance has a significant relationship. Simultaneously, the study also found that both variables have an effect on food inflation. This research provides a new perspective on the role of MSMEs in Indonesia's post-pandemic food security, and proposes more comprehensive and Islamic economy-based policies to support the sustainability of MSMEs and food security in Indonesia.